The gap between technology awareness and adoption in Sub-Saharan Africa: A literature review for the DeSIRA project - Kazembe, Cynthia (International Food Policy Research Institute, 2021)
This paper reviews different studies on technology adoption in sub-Saharan Africa to understand the determinants of low adoption of improved technologies, with a special focus on Malawi. This will in turn help explain why there is a gap between awareness and adoption of agriculture technologies. As evidenced from the results of the FGDs conducted in Malawi in 2018, despite the visible benefits of the new technologies, farmers often do not adopt or take a long time to adopt them. This creates a gap between awareness of agriculture technologies and their adoption. The existing literature from sub-Saharan Saharan Africa, demonstrates that adoption, as a decision-making process, is affected by farmers’ access to information, their financial and human capital, incentives and external programs, plus farmers’ attitude to risk.